(3JHUQI CQHGH GdGdHGH aj cjajI GdfLGI aj GdMQhH ef GdCShGA hfTQ CYdGe GdCYdGe aj GdYOO hGdBdGJs - (3eQVj Hf Ydj Hf eQVj GdWQShSj,J (B589 (3g` s ((3eMeO Hf SdjeGf s)
(3ChdgG (B:s
(3GdMeO ddg CeG HYO , adeG aWQ Gddg JYGdi ehdGfG hSjOfG Gdedc GdfGUQ s
(3BNQgG (B:s
(3hEfeG GdeQA MOjK HYOg acf MOjKkG MSfkG def hYi hGdMeO ddg QH GdYGdejf s
(3NWhW eNJdaIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B203s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B9 s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs